Estudo do ensaio de destacamento (Pullout) para fibras vegetais inseridas em compósitos cimentícios - Romão, Riacrdo Manoel (Universidade Federal de São Carlos, 2024)
Various materials are employed daily in the civil construction sector, each with distinct raw materials, resulting in diverse properties and applications. This sector is in constant evolution due to the continuous realization of new projects. With the growing demand for sustainability in all sectors of society, there arises the need to harness materials that were previously simply discarded. This implies a more effective utilization of generated waste, also alleviating the pressure on environmental resources whose acquisition or use significantly impacts the environment. One strategy to achieve this goal is the development of new materials that make use of previously purposeless waste. Among these materials, composites stand out, formed by a matrix whose characteristics are enhanced through the combination with a reinforcing material. Among the options for reinforcing materials are plant fibers, which, on their own, present a wide variety, each with its distinct characteristics. Therefore, studies that seek to assess the specific behavior of each type of fiber as reinforcement, as well as the methodology used for this evaluation, are crucial for the development of alternative materials that meet current needs and provide a broader range of materials with distinct applications for the market. One of the methodologies employed to assess the incorporation of plant fibers in cementitious matrices is the pullout test. This test allows testing the effectiveness of the bond between the fiber and the matrix, as well as determining the critical length of the fiber, a crucial factor for evaluating the transmission of forces in the material when subjected to a force. In this context, the present study aimed to investigate the pullout test methodology through the testing of composite materials with cementitious matrices reinforced with green coconut fiber ( Cocos nucifera L. ).
Study of the pullout test for plant fibers embedded in cementitious composites
Keywords: Construção civil; Ensaio de Pullout; Fibra de coco; Material alternativo; Sustentabilidade; Non-conventional material; Civil construction; Coconut fiber; Pullout test; Sustainability; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL